Creating A Better Competitive Edge Through Environmental Sustainability: A Case Study of Panasonic - Daisy Mui Hung Kee; Tiveeya Sri Saravanan; Sharnitra Sridaran; Syazwina Syahrin; Tulasii Rajandran; Jiale Tian; Huayan Zhang (International Journal of Applied Business and International Management, 2020)
This paper investigates Panasonic's strategies for its better competitive edge through environmental sustainability. The study analyzed the data collected from the company's websites, customers' personal experiences, and questionnaires. The surveys on customers' feedback on Panasonic products and services were carried out. This study's literature contribution value lies in its investigation of how Panasonic's environmental sustainability has led the company to a competitive advantage. The findings of this paper have significant importance since people today are more concerned about environmental sustainability. Strategies and practices that create a sustainable world economy were discussed.